Model Ekowisata Urban dalam Kawasan Pusat Pemerintahan Ibu Kota Nusantara: Model Ekowisata Urban dalam Kawasan Pusat Pemerintahan Ibu Kota Nusantara - Dananjaya, Ahmad Ghazy; Faarhan, Muhammad Rakatama (Jurnal Ilmiah Ilmu Pariwisata, 2025)
This study aims to examine the model of urban ecotourism in the development of the central government area of the Nusantara Capital City (IKN), focusing on sustainability and the integration of tourism with the green city concept. Using a mixed-methods approach, this research combines qualitative and quantitative data analysis involving 400 respondents. The study evaluates the potential and challenges of urban ecotourism development, including the management of natural attractions, accessibility, accommodation facilities, and interactions between tourists and local communities. The social aspect analyzed includes the impact on the social structure and inequalities caused by tourism. The economic impact includes job creation and increased local income, while the environmental impact assesses the risk of environmental degradation due to mass tourism. Through in-depth interviews and quantitative surveys, this research is expected to provide a comprehensive overview of the sustainable urban ecotourism model implementation in IKN and offer policy recommendations for environmentally and socially responsible tourism planning and management in IKN.